Mean-Value Theorem - Trohimchuk, Yu. Yu (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We propose a new approach to the classical mean-value theorem in which two mean values are used instead of one. This approach is of especial importance for complex functions because there are no available theorems of this kind for these functions.